THE ROLE OF EVENT ATTENDEES’ KNOWLEDGE, ENTHUSIASMS, AND ACTIVENESS ON COMMUNITY INVOLVEMENT - Christina Rahardja Honantha (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
Today, events are central to our culture as perhaps never before. Increases in leisure time anddiscretionary spending have led to a proliferation of public events, celebrations andentertainment. The event marketing manager must then examine the objectives of these majorplayers – what each of them expects to gain from the event, and what forces acting on them arelikely to affect their response to the event. This study to examine the relationships among eventattendees' knowledge of an event sponsor's products and activeness and enthusiasm related to thearea of the event for a sponsor’s community involvement. This approach assumes that marketers,by adopting a consumer focus, respond only to the expressed needs of event visitors. In reality,sound marketing research can unveil the latent needs of consumers that only innovative eventscan satisfy. Event marketing is defined as the